18S rDNA phylogeny of Pseudo-nitzschia (Bacillariophyceae) inferred from sequence-structure information. Issue 2 (1st March 2016) - Lim, Hong Chang; Teng, Sing Tung; Lim, Po Teen; Wolf, Matthias; Leaw, Chui Pin
Abstract: We explored the 18S rDNA sequences of Pseudo - nitzschia and its close relatives, together with their individual secondary structure information to reconstruct phylogenies. Forty-eight taxa classified in the Bacillariaceae and Achnanthaceae were analyzed by character-based (maximum parsimony and maximum likelihood) and distance-based (neighbour-joining) methods. Three raphid diatoms from the Eunotiaceae were used as out-groups. The sequence-structure alignment was generated by 4SALE (i.e. a one-letter encoded alignment that contained the individual secondary structure information) and applied to the character-based phylogeny reconstruction. All analyses highly support Pseudo - nitzschia + Fragilariopsis as monophyletic. The Pseudo - nitzschia / Fragilariopsis clade is further divided into three subclades. One clade comprises members in the P. seriata and P. americana complexes and species of Fragilariopsis ; the second and third clades constitute members in P. pseudodelicatissima and P. delicatissima complexes. Among all analyses, the distance-based method yielded a more highly resolved phylogenetic framework for the Pseudo - nitzschia / Fragilariopsis clade than did the character-based analyses. Other than those currently known genetic markers, 18S rDNA was also useful in exploring the intrageneric relationships.